O museu de ciência como cenário da formação docente: saberes e concepções de licenciandos mediadores do Museu Seara da Ciência - UFC - Silva, Maria Cleidiane Barbosa da (2018)
The current research was outlined from the need to understand science museum as an institution that promotes science and contributes with the formation of educators. The main goal of this research was to identify the general contribution of the science museum Seara da Ciênca for the formation of educators of natural sciences. The theoretical rationale that supports the discussion connects concepts from the field of education on science museums, such as the contributions of Marandino (2001, 2003, 2008, 2009); Falk and Dierking (1992) and Queiroz et al., (2002) in dialogue with the teaching knowledge by Tardif (2014) and Carvalho and Gil-Pérez (1995). The research was conducted in the science museum Seara da Ciênca, a promoter of science and technology of the Federal University of Ceara (UFC). The subjects of the research were six scholarship holders who are undergraduate students of the programs of Chemical, Physics and Biological Sciences from the UFC. The research is based on the qualitative, descriptive and explanatory approaches. The adopted method of research is a Case of Study. The procedures of data collecting were: documental analyses, observation and semi-structured interviewing. The results show that the context of educators’ formation identified at the Seara da Ciência is based on the assembled knowledge in the activities of science promotion mediated by the scholarship holders. As mediators, the scholarship holders get in touch with the scientific culture of the science museum and share their knowledge with visiting schools and with the formation in science, which are important experiences to build-up perceptions that create the concepts of Education, Science and Scientific Promotion. It was observed that the framework of educators’ formation receives interference from sectors that manage the scholarships devoted to Extension and Academic Initiation. The main conclusions highlight that the science museum Seara da Ciência supports the formation of science educators through the reshaping of the meaning on teaching and learning of science that occurs outside the spaces of formal education. It is understood that the formation of educators in the field of natural sciences is not limited to the academia during the undergraduate programs, it should also include other relating experiences, such as actions in extension centers and internships in non-formal educational spaces.